2017
DOI: 10.3390/ijms18061257
|View full text |Cite
|
Sign up to set email alerts
|

Wound-Healing Studies in Cornea and Skin: Parallels, Differences and Opportunities

Abstract: The cornea and the skin are both organs that provide the outer barrier of the body. Both tissues have developed intrinsic mechanisms that protect the organism from a wide range of external threats, but at the same time also enable rapid restoration of tissue integrity and organ-specific function. The easy accessibility makes the skin an attractive model system to study tissue damage and repair. Findings from skin research have contributed to unravelling novel fundamental principles in regenerative biology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
141
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 200 publications
(234 reference statements)
4
141
0
2
Order By: Relevance
“…Corneal cells express a variety of growth factors and cytokines that have special e ects on epithelial cells. It is activated during corneal wound healing and plays a major role in corneal in ammation and angiogenesis [27]. THE KEGG pathway analysis also indicated that the DEGs were mainly enriched in Neuroactive ligand-receptor interaction and Cytokinecytokine receptor interaction, this is consistent with our T 2: e top 15 hub genes rank in cytoHubba.…”
Section: Hub Gene Selectionsupporting
confidence: 86%
“…Corneal cells express a variety of growth factors and cytokines that have special e ects on epithelial cells. It is activated during corneal wound healing and plays a major role in corneal in ammation and angiogenesis [27]. THE KEGG pathway analysis also indicated that the DEGs were mainly enriched in Neuroactive ligand-receptor interaction and Cytokinecytokine receptor interaction, this is consistent with our T 2: e top 15 hub genes rank in cytoHubba.…”
Section: Hub Gene Selectionsupporting
confidence: 86%
“…Corneal wound repair is different from the repair of other tissues owing to several unique features. 13 First, the absence of blood and lymphatic vessels limits the relative number of inflammatory cells trafficking to the wound after a corneal injury.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Upon corneal injury, the quiescent CSKs become activated and change phenotype into stromal fibroblasts (SFs), which are proliferative and produce repair-type extracellular matrix (ECM) components (e.g., fibronectin, proteinases, and a5-integrin) in the event of wound healing. [4][5][6] SFs can further transform into myofibroblasts resulting in scar formation, and the fibrotic tissues interfere with or obstruct light transmission, resulting in reduced visual acuity and eventually vision loss. 7,8 Trauma, infection, degeneration, and immunologic disorders (e.g., keratoconus), inherited diseases, and/or refractive surgeries can lead to CSK death, and the surviving keratocytes can transit to SFs, causing haze development and even opacification when myofibroblasts are present.…”
mentioning
confidence: 99%